2014
DOI: 10.1039/c3fo60705d
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of hypocholesterolemic effect and antioxidant activity of Boops boops proteins in cholesterol-fed rats

Abstract: Dietary proteins affect blood cholesterol concentrations and antioxidant status, which are related to several diseases, including cardiovascular disease. The present study attempts to investigate the potential of Boops boops proteins (Bb-NHP) and its hydrolysate (Bb-HP) in the prevention of hypercholesterolemia and oxidative stress in rats fed a high cholesterol diet (HCD). After four weeks' treatment, serum lipid profiles (total cholesterol, triglycerides, HDL-cholesterol and LDL-cholesterol), the activities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 36 publications
9
19
0
Order By: Relevance
“…Further, oral administration of Fluv and FSPHs increased the HDL-c levels compared to the corresponding values of HCD group and the value obtained were even higher than that of control group. Similar results were also reported by Lassoued et al [11] with protein hydrolysates from Boops boops and Ktari et al [10] with protein hydrolystes from Salaria bascilisca. Ben Khaled et al [9] also reported that sardinelle protein hydrolysates obtained by enzymatic hydrolysis help to balance the serum lipid profile in rats fed a high-fat diet.…”
Section: Effect Of Fsphs On Serum Lipid Parameterssupporting
confidence: 89%
See 1 more Smart Citation
“…Further, oral administration of Fluv and FSPHs increased the HDL-c levels compared to the corresponding values of HCD group and the value obtained were even higher than that of control group. Similar results were also reported by Lassoued et al [11] with protein hydrolysates from Boops boops and Ktari et al [10] with protein hydrolystes from Salaria bascilisca. Ben Khaled et al [9] also reported that sardinelle protein hydrolysates obtained by enzymatic hydrolysis help to balance the serum lipid profile in rats fed a high-fat diet.…”
Section: Effect Of Fsphs On Serum Lipid Parameterssupporting
confidence: 89%
“…Several works have reported the importance of dietary proteins and protein hydrolysates in the regulation of cholesterol metabolism [9,10,11]. To date, hypocholesterolemic properties have been reported for soy [12] and whey [13].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, when hyperlipidemic mice were supplemented with FPH, these activities decreased and became comparable to the control group. Similar findings were observed in previous studies showing the hepatoprotective effects of protein hydrolysates on hypercholesteromic rats [20].…”
Section: Discussionsupporting
confidence: 92%
“…We have previously demonstrated that hypercholesterolemia was associated with the deterioration of antioxidant status, resulting from increased MDA levels and decreased antioxidant enzyme activity [36]; in our experimental design, we studied whether deterioration of antioxidant status associated with hypercholesterolemia was corrected by fish protein hydrolysates. In the present study, results showed that sardine and particularly sardinelle decreased TBARS and hydroperoxides in serum.…”
Section: Discussionmentioning
confidence: 99%